Autoerotic deaths : practical forensic and investigative perspectives - Sauvageau, Anny; Geberth, Vernon J. (Boca Raton, Florida : CRC Press, 2013)
'Preface Autoerotic Deaths Practical Forensic and Investigative Perspectives is the result of a meticulous collaboration and friendship between a former New York detective and homicide commander, who is now an international homicide and forensic consultant, and an experienced forensic pathologist, who is the chief medical examiner of Alberta and an internationally recognized authority on asphyxial death. This book is the result of a unique combination of the knowledge and experience of a dedicated murder cop who has seen it all and that of a passionate scientist whose research in the field has modernized the concepts around autoerotic deaths. The two authors have enjoyed multiple conversations during which the new data of the science met the concrete examples of case studies. This is what this book is all about: presenting a scientific modern view of autoerotic death, with case illustrations. Autoerotic Deaths: Practical Forensic and Investigative Perspectives will become the benchmark and'best practice' model for professional death investigations involving autoerotic deaths because it will provide practical and conventional information based on scientific research and case experience from the field with a wide variety of exquisite case histories. Throughout this textbook, we reference additional resource information as well as case examples of the application of various tactics, procedures, and forensic techniques along with full-color illustrations, explanations, and tables to assist the reader in understanding the dynamics of autoerotic deaths'--
Includes bibliographical references and index.
Keywords: Autoerotic asphyxia; Autoerotic death; Accidents; Forensic pathology; Paraphilias -- psychology; Suicidal Ideation; Asphyxia; Fatal Outcome